Perceived Connection to Instructor and Instructor Passion as Predictors of Transformative Experiences in Science - Kevin J. Pugh; Cassendra M. Bergstrom; Michael M. Phillips; Julie M. Sexton; Colton Olson; Eric M. Riggs (MDPI AG, 2023)
Transformative experience represents a deep-engagement construct and refers to experiences in which students use science content to see and experience the world in meaningful new ways outside the classroom. Such experiences are associated with deep learning (e.g., transfer) and engagement (e.g., academic and career choice) outcomes. However, research on individual factors predictive of transformative experience is limited. The current study investigated university geoscience students' perceptions of a connection to their instructor(s) and perceptions of their instructors' passion for the content as predictors of transformative experience. Controlling for students' initial interest and self-efficacy in the domain, we found both these factors to be predictive of transformative experience. These results suggest science teachers may be able to support engagement in transformative experiences by connecting with students and expressing a passion for the content.